2017
DOI: 10.1155/2017/1869091
|View full text |Cite
|
Sign up to set email alerts
|

Prediction of Severity of Acute Pancreatitis Using Total Serum Calcium and Albumin-Corrected Calcium: A Prospective Study in Tertiary Center Hospital in Nepal

Abstract: Introduction Total calcium (TC) and albumin-corrected calcium (ACC) are easily accessible AP severity tests in the Primary Health Care Center of Nepal. The aim of the study was to evaluate TC and ACC as prognostic severity markers in acute pancreatitis (AP). Methods All patients admitted in Tribhuvan University Teaching Hospital with the diagnosis of AP were studied prospectively over a period of one year from January 2015 to January 2016. TC and ACC were measured in the first 24 hours of admission in each pat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 18 publications
1
6
0
Order By: Relevance
“…In this work, age, sex and etiology of AP were statistically non-significant different between both groups. This agrees with Pokharel et al [14] who reported that the severity of AP was not related to the age or sex of the patient. Similarly, there was no association between etiology and severity of AP.…”
Section: Discussionsupporting
confidence: 93%
“…In this work, age, sex and etiology of AP were statistically non-significant different between both groups. This agrees with Pokharel et al [14] who reported that the severity of AP was not related to the age or sex of the patient. Similarly, there was no association between etiology and severity of AP.…”
Section: Discussionsupporting
confidence: 93%
“…Although studies on AP have been conducted in Nepal, there is no study that has examined FS among patients with AP. A previous study from our center noted biochemical markers, total serum calcium and albumin-corrected calcium, are useful severity predictors in AP [ 18 ]. Our study further adds that median FS 48 is a useful parameter as increased median FS 48 was observed in more severe AP.…”
Section: Discussionmentioning
confidence: 99%
“…When comparing the sensitivity, specificity, and predictive values of Total calcium to those of [3] we found that our sensitivity was significantly greater. The higher cutoff value could explain the improved [16,15]. so, determination of serum calcium levels is a direct biochemical measure that is regularly performed in the majority of hospital settings.…”
Section: Discussionmentioning
confidence: 99%